Removal of copper ions from aqueous solution using adlai shell (Coix lacryma-jobi L.) adsorbents - Flores, Edgar D. (College of Engineering, University of the Philippines Diliman, 2014)
Copper Cu (II) ions in wastewaters are toxic to humans and aquatic organisms even at low concentrations. In this study, adlai shell (Coix lacryma-jobi L.) adsorbents were used for the removal of copper ions from aqueous solution. The effects of adsorbent particle size, initial pH of the solution, initial Cu (II) concentration and adsorbent pre-treatment on copper removal were evaluated. The amount of Cu (II) removed was highest at lowest particle size and at pH 6. Adsorption capacity increased with initial Cu (II) concentration and contact time. Pretreatment improved the adsorption capacities of adlai shell for Cu (II) ions from 11.21 mg/g for untreated to 13.76mg/g and 14.58 mg/g for carbonized and acid-treated carbonized respectively at 298 K. This further improved to 13.60 mg/g for untreated, 16.70 mg/g for carbonized and 17.04 mg/g for acid-treated carbonized at 318 K. The kinetics of the adsorption system is best described by the pseudo second order equation (R2=0.9999). The theoretical qe values (1.97, 8.66 and 17.12 mg/g) provided by the pseudo-second order equation, were in good agreement with the experimental qe values (1.94, 8.48 and 16.74 mg/g). In addition, the high coefficient of determination (R2) for the intraparticle diffusion model indicates that the rate-determining step is a combination of chemisorption and pore diffusion at lower concentration (10 mg/L) while at higher concentrations (50 to 100 mg/L) are a combination of boundary layer, pore diffusion and chemisorptions. The Freundlich model adequately describes the equilibrium data. The high coefficient of determination values (R2>0.9636) of the Freundlich model is validated by its n values (1.7473-1.9232), signifying favorable heterogeneous adsorption between the adlai shells and Cu (II) ions). For thermodynamic studies, the positive values of ΔH0 suggest that Cu (II) adsorption onto adlai shells was endothermic while the negative values of ΔG0 suggest that Cu (II) adsorption onto adlai shells was favorable and spontaneous. Generally, the results of the study demonstrates the potential of adlai shells as an effective adsorbent for the removal of Cu (II) ions from aqueous solutions.